2018
DOI: 10.1097/sap.0000000000001351
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide and Cyanide Poisoning in the Burned Pregnant Patient

Abstract: Carbon monoxide (CO) is a small molecule poison released as a product of incomplete combustion. Carbon monoxide binds hemoglobin, reducing oxygen delivery. This effect is exacerbated in the burned pregnant patient by fetal hemoglobin that binds CO 2.5- to 3-fold stronger than maternal hemoglobin. With no signature clinical symptom, diagnosis depends on patient injury history, elevated carboxyhemoglobin levels, and alterations in mental status. The standard of care for treatment of CO intoxication is 100% normo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 102 publications
(174 reference statements)
0
10
0
Order By: Relevance
“…Long-term exposure to low concentrations of CO can cause dizziness, vomiting, difficulty breathing, and muscle weakness. Even though CO is toxic to humans at high concentrations, many studies have documented that low-doses exogenous CO (approximately 250–500 ppm) have protective function against various human diseases [7] , [8] . In this study, we suggest that CO derived from CORM-2 can possibly be used as a therapeutic for lung inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term exposure to low concentrations of CO can cause dizziness, vomiting, difficulty breathing, and muscle weakness. Even though CO is toxic to humans at high concentrations, many studies have documented that low-doses exogenous CO (approximately 250–500 ppm) have protective function against various human diseases [7] , [8] . In this study, we suggest that CO derived from CORM-2 can possibly be used as a therapeutic for lung inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon monoxide (CO) is currently known to be generated in cells or tissues as a byproduct of heme oxygenase (HO) after heme catalytic activity [6] . Even though CO is toxic to humans at high concentrations, many studies have documented that low-doses exogenous CO (approximately 250–500 ppm) have protective function against various human diseases [7] , [8] . Previous studies have confirmed that low concentrations of CO or CO-releasing molecules (CORMs) can eliminate microorganisms [9] , regulate cell death [10] , and resist inflammation [10] .…”
Section: Introductionmentioning
confidence: 99%
“…They are often used as a means of chemical terrorism [45,48]. In addition, during World War II, the Nazis used cyanide as a means of genocide in gas chambers [21,22,40,54,55]. Certain anticancer drugs contain cyanide groups.…”
Section: Problem Articlesmentioning
confidence: 99%
“…The first signs are bitterness in the mouth, sore throat, laryngospasm, dizziness, excessive salivation, nausea, vomiting, shortness of breath and confusion. But the severity of these mani-festations decreases a few hours after the removal of the victim from the contaminated area and the use of antidote therapy [38][39][40][41][42][43][44][49][50][51][52][53][54][55]. The action of cyanide in low concentration in the atmospheric air causes the development of minor symptoms, in particular the appearance of a feeling of fear, headache, vomiting, shortness of breath, sometimes with the smell of bitter almonds and dizziness.…”
Section: Problem Articlesmentioning
confidence: 99%
“…A case report showed a COHb measurement of 61% at fetal autopsy, although the mother had a measurement of 7% after just an hour's O 2 treatment. For this reason, some authors regard pregnancy as a strict indication for HBOT (23), especially in the presence of neurological symptoms, signs of fetal stress, occurrence of syncope, or high COHb levels (4).…”
Section: Pregnant Women and Childrenmentioning
confidence: 99%